Implementation Of Criminal Sanctions Against Crime Mining Potential Effects Without Permission For Deterrent Effect (Study On Jurisdiction Central Java Regional Police) - Nizar Anwar; Anis Mashdurohatun (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study, entitled